Describing the Patient Journey Through Healthcare Pathways Following Mild Traumatic Brain Injury in New Zealand Using Novel Graph Analysis - Bastos Gottgtroy, Renata; Hume, Patria A; Theadom, Alice (Taylor and Francis Group, 2023)
AIM: To identify treatment provider sequences and healthcare pathway characteristics and outcomes for people with mild traumatic brain injury (mTBI) in New Zealand. METHODS: Total mTBI costs and key pathway characteristics were analysed using national healthcare data (patient's injury and services provided). Graph analysis produced sequences of treatment provider types for claims with more than one appointment and healthcare outcomes (costs and time to exit pathway) were compared. Key pathway characteristics' effect on healthcare outcomes were evaluated. RESULTS: In two years, 55,494 accepted mTBI claims cost ACC USD$93,647,261 over four years. For claims with more than one appointment (36%), healthcare pathways had a median 49 days (IQR, 12-185). The 89 treatment provider types resulted in 3,396 different provider sequences of which 25% were General Practitioners only (GP), 13% Emergency Department to GP (ED-GP) and 5% GP to Concussion Service (GP-CS). Pathways with shorter time to exit and lower costs had correct mTBI diagnosis at initial appointment. Income maintenance comprised 52% of costs but only occurred for 20% claims. CONCLUSIONS: Improving healthcare pathways for people with mTBI by investing in training of providers to enable correct mTBI diagnosis could yield longer term cost savings. Interventions to reduce income maintenance costs are recommended.
Keywords: Concussion; care pathway; costs; mild traumatic brain injury; treatment; 4203 Health Services and Systems; 42 Health Sciences; Clinical Research; Traumatic Brain Injury (TBI); Health Services; Neurosciences; Brain Disorders; Traumatic Head and Spine Injury; Physical Injury - Accidents and Adverse Effects; 8.2 Health and welfare economics; 8 Health and social care services research; 3 Good Health and Well Being; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; Rehabilitation; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; 5203 Clinical and health psychology; Humans; Brain Concussion; New Zealand; Delivery of Health Care; Humans; Brain Concussion; Delivery of Health Care; New Zealand; Humans; Brain Concussion; New Zealand; Delivery of Health Care